Mice with different susceptibility to tick-borne encephalitis virus infection show selective neutralizing antibody response and inflammatory reaction in the central nervous system - Palus, Martin; Vojtíšková, Jarmila; Salát, Jiří; Kopecký, Jan; Grubhoffer, Libor; Lipoldová, Marie; Demant, Peter; Růžek, Daniel (Journal of neuroinflammation, 2013)
BACKGROUND: The clinical course of tick-borne encephalitis (TBE), a disease caused by TBE virus, ranges from asymptomatic or mild influenza-like infection to severe debilitating encephalitis or encephalomyelitis. Despite the medical importance of this disease, some crucial steps in the development of encephalitis remain poorly understood. In particular, the basis of the disease severity is largely unknown. METHODS: TBE virus growth, neutralizing antibody response, key cytokine and chemokine mRNA production and changes in mRNA levels of cell surface markers of immunocompetent cells in brain were measured in mice with different susceptibilities to TBE virus infection. RESULTS: An animal model of TBE based on BALB/c-c-STS/A (CcS/Dem) recombinant congenic mouse strains showing different severities of the infection in relation to the host genetic background was developed. After subcutaneous inoculation of TBE virus, BALB/c mice showed medium susceptibility to the infection, STS mice were resistant, and CcS-11 mice were highly susceptible. The resistant STS mice showed lower and delayed viremia, lower virus production in the brain and low cytokine/chemokine mRNA production, but had a strong neutralizing antibody response. The most sensitive strain (CcS-11) failed in production of neutralizing antibodies, but exhibited strong cytokine/chemokine mRNA production in the brain. After intracerebral inoculation, all mouse strains were sensitive to the infection and had similar virus production in the brain, but STS mice survived significantly longer than CcS-11 mice. These two strains also differed in the expression of key cytokines/chemokines, particularly interferon gamma-induced protein 10 (IP-10/CXCL10) and monocyte chemotactic protein-1 (MCP-1/CCL2) in the brain. CONCLUSIONS: Our data indicate that the genetic control is an important factor influencing the clinical course of TBE. High neutralizing antibody response might be crucial for preventing host fatality, but high expression of various cytokines/chemokines during TBE can mediate immunopathology and be associated with more severe course of the infection and increased fatality.
Keywords: virová nálož; RNA, Messenger; neutralizující protilátky; Chemokines; protilátky virové; Inflammation; kvantitativní polymerázová řetězová reakce; Genotype; odolnost vůči nemocem; membránové proteiny; cytokiny; Membrane Proteins; myši inbrední BALB C; Encephalitis Viruses, Tick-Borne; Disease Susceptibility; Real-Time Polymerase Chain Reaction; Mice, Inbred BALB C; Viral Load; zánět; Encephalitis, Tick-Borne; Disease Resistance; Viral Plaque Assay; Animals; buněčná imunita; zvířata; klíšťová encefalitida; Antibodies, Neutralizing; mozek - chemie; Immunity, Cellular; centrální nervový systém; myši; Brain Chemistry; genotyp; viry klíšťové encefalitidy; Antibodies, Viral; Cytokines; plakové testy; Central Nervous System; Mice; náchylnost k nemoci; messenger RNA; chemokiny